Social Capital of The Religious Society of Kediri City: Inclusiveness of Multicultural Education Based on Local Wisdom - Moch. Muwaffiqillah (Didaktika Religia, 2021)
his study seeks to describe a portrait of the social situation, harmony, and harmony of religious communities in Kediri City, East Java. The photoshoot of the social situation is not without reason. The people of Kediri are known as the most tolerant, solid, and cooperative society in the middle of all differences in religion, ethnicity, and ethnicity between them. It isn't easy to find a depiction of this pattern of religiosity in a multicultural society. Differences often lead to conflicts and social feuds. The developed hypothesis is that there are subsystems attached to every social pattern of the Kediri community, including the social capital of the community and multicultural education based on aspects of the local wisdom of the Kediri community. Therefore, the author is moved to reveal this reality by using a field-based qualitative research approach and selecting informants based on the purposive sampling method with the snowballing. Data were extracted using poles, interviews, observations, and documentation. The study results reveal two things, namely 1) social capital built in a religious society based on social harmony. Boding social capital, business networking, business partners, bridging social capital, and all stakeholders, the business character of the people of Kediri City is based on a philosophy of life such as guanxi and ukhuwah. 2) social capital is combined with multicultural education in the city of Kediri by issuing a policy of "education for all groups" without considering ethnic, cultural, ethnic, religious, and linguistic differences. The concept of multicultural education is divided into two patterns; education for all and the filtering of local Kediri culture as a bulwark of social harmony.